Upaya Meningkatkan Kemampuan Pedagogik Guru melalui Pelaksanaan Supervisi Klinis di Sekolah Dasar 07/X Parit Culum 1 Kecamatan Muara Sabak Barat Kabupaten Tanjung Jabung Timur Tahun 2021 - Jumasril Jumasril (Universitas Batanghari Jambi, 2022)
State Elementary School 07/X Parit Culum I, Muara Sabak Barat District, Tanjung Jabung Timur Regency, which consists of 16 teaching staff, in practice, is not optimal and may not even be carried out the same way. This is evidenced by the results of the initial assessment of the cycle, it was obtained that 6 teaching staff were still in poor assessment criteria so that none of the teaching staff had achieved the assessment criteria in a good category. The purpose of the study was to improve the pedagogical competence of teachers at the State Elementary School 07/X Parit Culum I, Muara Sabak Barat District. This research is a school action research (School Action Research). This research takes the form of school action research (PTS), namely the ability of the principal in preparing school administration through the implementation of managerial supervision. Cycle I which was carried out for 6 Class Teachers was running effectively, although overall the expected results had not been achieved, because of the 6 Class Teachers there were 2 Class Teachers or 33.3% who stated that their pedagogic competence had increased when compared to the initial conditions before the implementation. pedagogical competency assessment activities are carried out. The implementation of the pedagogical competency assessment activities carried out in Cycle II to 6 Class Teachers went well, overall the expected results have been achieved, because of the 6 Class Teachers, all of them have stated that their pedagogical competence has increased with the GOOD category as many as 3 people or 50% and VERY GOOD as much as 50% or 3 Class Teachers.